POSITIVE HEALTH AMONGST OLDER TRAVELLERS AND OLDER HOMELESS PEOPLE: LIFE-COURSE AND STRUCTURAL DETERMINANTS. (11th November 2018) - Walsh, K; O'Donovan, D; Scharf, T; O'Shea, E; Macfarlane, A
Abstract: Evidence indicates that older members of the Traveller and homeless communities in Ireland are more likely to experience health inequalities. Nevertheless, the ageing-profile and diversity of older Traveller and older homeless (OTOH) populations indicate increasingly heterogeneous health trajectories and growing intra-group health differences. Little is known about the diversity of these experiences, the OTOH who come to achieve more positive outcomes and what this patterns might mean for developing effective community and primary care models for these and other marginalized groups. As a part of a larger qualitative voice-led study, this paper presents a scoping review of the international literature on life-course and structural determinants of positive subjective health amongst OTOH people. Findings indicate that although specific morbidity pathologies differ, these groups experience similar socio-cultural and political displacement, impacting to different degrees on health experiences. Different constructions of positive health and the associations with life-course critical events will be presented.